Fishermen and Little Fish: Migration and Hospitality in Maxine Beneba Clarke’s ‘The Stilt Fishermen of Kathaluwa’ - Natalie Edwards; Christopher Hogarth (PORTAL: Journal of Multidisciplinary International Studies, 2016)
In this article, we argue that Maxine Beneba Clarke’s tale ‘The Stilt Fishermen of Kathaluwa,’ in Foreign Soil (2014), is a provocative representation of migration in contemporary Australia. At a time in which the world is facing its largest migration since the Second World War and in which Australian border policy is making headlines around the world, Clarke’s tale is a powerful intervention in discourses of contemporary Australian identity and nationhood. We demonstrate that the tale is a subtle manipulation of what McCullough terms the ‘refugee narrative structure’ since it carefully undercuts the myth of a nation as a coherent narrative across time and space. By juxtaposing the tales of an illegal migrant and a volunteer case worker, and by setting the tale largely in a functioning detention centre, Clarke gives voice to the voiceless and draws parallels between individuals on different sides of the insider/outsider binary. The encounter that finally takes place between them implicates the reader very directly in discourses of contemporary migration and border policy.